The Role of Power in EU–Russia Energy Relations: The Interplay between Markets and Geopolitics. Issue 10 (26th November 2018) - Siddi, Marco
Abstract: Energy trade is an essential factor in EU–Russia relations. This essay argues that Russia and the European Union have deployed two types of power in their post-Cold War energy relationship. Russia has predominantly exerted geopolitical power through the sale of its vast energy resources and selected strategies to channel them to partners. With a large market but lacking fossil fuels, the EU attempted to achieve its aims mostly through regulatory power. However, both the Russian and the EU external energy policy strategies have recently become more nuanced. This evolution in their approaches has resulted in Russia's gradual acceptance of the regulatory and market principles promoted by the EU.